A comparative look at structural variation among RC-LH1 'Core' complexes present in anoxygenic phototrophic bacteria - Gardiner, Alastair T; Nguyen-Phan, Tu C; Cogdell, Richard J (Photosynthesis research, 2020)
All purple photosynthetic bacteria contain RC-LH1 'Core' complexes. The structure of this complex from Rhodobacter sphaeroides, Rhodopseudomonas palustris and Thermochromatium tepidum has been solved using X-ray crystallography. Recently, the application of single particle cryo-EM has revolutionised structural biology and the structure of the RC-LH1 'Core' complex from Blastochloris viridis has been solved using this technique, as well as the complex from the non-purple Chloroflexi species, Roseiflexus castenholzii. It is apparent that these structures are variations on a theme, although with a greater degree of structural diversity within them than previously thought. Furthermore, it has recently been discovered that the only phototrophic representative from the phylum Gemmatimonadetes, Gemmatimonas phototrophica, also contains a RC-LH1 'Core' complex. At present only a low-resolution EM-projection map exists but this shows that the Gemmatimonas phototrophica complex contains a double LH1 ring. This short review compares these different structures and looks at the functional significance of these variations from two main standpoints: energy transfer and quinone exchange.
Keywords: světlosběrné proteinové komplexy; Models, Molecular; Rhodobacter sphaeroides; Energy Transfer; RC–LH1; Rhodopseudomonas; Structures; genetická variace; Purple photosynthetic bacteria; fotosyntéza; Reaction centres; Genetic Variation; Bacterial Proteins; Photosynthetic Reaction Center Complex Proteins; fotosyntetická reakční centra (proteinové komplexy); Protein Conformation; molekulární modely; vztahy mezi strukturou a aktivitou; Benzoquinones; Light-Harvesting Protein Complexes; Photosynthesis; přenos energie; Chromatiaceae; benzochinony; Anoxygenic phototrophs; bakteriální proteiny; Structure-Activity Relationship; konformace proteinů; Light harvesting